Improving the quality of human resources in Ciburuy village staff to improve the quality of public services - Deden Ardiansyah (Research Collaboration Community (RCC), 2020)
Utilization of computer technology to improve the quality of public services in Ciburuy village cannot be carried out optimally if it is not supported by the readiness of human resources as the parties who use it. readiness of human resources in using computer technology is one of the important factors in terms of public services.Therefore we need a computer technology transfer process that is adequate, right on target and appropriate for Ciburuy village staff, as the main actor in this activity, namely service to the community.Methods of implementing human resource improvement through computer skills training activities through the Microsoft Word Application Program, Microsoft Excel, Microsoft Power Point, databases and networks are carried out through several stages. resulting in an average value of being satisfied and quite satisfied so that public services in Ciburuy village must improve service quality. but the unique thing is seen in the ability of village staff in the service. so that respondents have started to feel satisfied with the services carried out by Ciburuy village staff.